2021
DOI: 10.1016/j.mehy.2020.110356
|View full text |Cite
|
Sign up to set email alerts
|

Development of integrated microfluidic platform coupled with Surface-enhanced Raman Spectroscopy for diagnosis of COVID-19

Abstract: Corona Virus Disease 19 (COVID-19) pandemic has created an alarming situation across the globe. Varieties of diagnostic protocols are being developed for the diagnosis of COVID-19. Many of these diagnostic protocols however, have limitations such as for example unacceptable no of false-positive and false-negative cases, particularly during the early stages of infection. At present, the real-time (quantitative) reverse transcriptase-polymerase chain reaction (RT-PCR) is considered the gold standard for COVID-19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 12 publications
0
60
0
2
Order By: Relevance
“…Microfluidic devices might also hold the answer for improving Coronavirus Disease 19 (COVID-19) testing. Amit Jadhav et al [ 91 ] proposed a diagnosis protocol based on surface-enhanced Raman spectroscopy coupled with microchips presenting integrated microchannels functionalized with vertically aligned Au/Ag-coated nanotubes or with disposable electrospun micro/nano-filter membranes. Such constructions can successfully trap viruses from various biological fluids.…”
Section: Applications Of Microfluidic Devicesmentioning
confidence: 99%
“…Microfluidic devices might also hold the answer for improving Coronavirus Disease 19 (COVID-19) testing. Amit Jadhav et al [ 91 ] proposed a diagnosis protocol based on surface-enhanced Raman spectroscopy coupled with microchips presenting integrated microchannels functionalized with vertically aligned Au/Ag-coated nanotubes or with disposable electrospun micro/nano-filter membranes. Such constructions can successfully trap viruses from various biological fluids.…”
Section: Applications Of Microfluidic Devicesmentioning
confidence: 99%
“…From the results of duplicated measurements for each sample, the consistency and repeatability of this SERS assay is 0.853 (Kendall coordination coefficient, p<0.01) and 4.5% (relative standard deviation, RSD) based on 1182/1189 ratio and 0.892 (Kendall coordination coefficient, p<0.01) and 4.2% (RSD) based on LD1 scores, respectively. Although the concept of using Raman spectroscopy to detect SARS-CoV-2 viruses has been raised by many researchers ( Lukose et al, 2021 ), these studies mainly focus on the detection sensitivity or substrate fabrication with artificial samples and there is no report on the detection of real environmental samples or accuracy ( Jadhav et al, 2021 ; Peng et al, 2021 ). Our findings proved the feasibility of ACE2@SN-SERS assay to on-site interrogate SARS-CoV-2 in real water samples, and both indicators have satisfactory performance.…”
Section: Resultsmentioning
confidence: 99%
“…A diagnostic of COVID-19 was developed based on surface-enhanced Raman scattering (SERS) combined with microfluidic systems that involve connected microchannels conjugated with Au/Ag-coated carbon nanotubes. The tool is used to detect viruses from various biological fluids, such as saliva, nasopharyngeal secretions, and tears [ 66 ]. Research demonstrated that the SERS technique could detect COVID-19 in polluted water at the single virus level.…”
Section: Detection Of Covid-19 Using Light Technologiesmentioning
confidence: 99%